An Algorithm to Balance an Unbalanced Transportation Problem to Achieve Improved Initial Solution - Tripti Sharma (International Journal of Mathematics And its Applications, 2018)
This paper suggests an algorithm to balance an unbalanced transportation problem in order to obtain improved initial feasible solution of unbalanced transportation problem proceed with Vogel's Approximation Method, in comparison to other existing algorithms to balance the transportation problem. The algorithm is supported by numerical examples.